IMPLEMENTASI METODE MUSYĀFAHAH DALAM MENINGKATKAN HAFALAN AL-QUR`AN JUZ 30 ANAK USIA DINI DI RA AL-FIRDAUS CIPAYUNG - Faza Karimatul Akhlak (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
The process of improving the memorization of the Qur'an for young children depends on the initial teaching from the teacher where the teacher can use various methods and methods in the process of memorizing the Qur'an in order to achieve the target memorization that has been set. The purpose of this study was to determine the application of the musyāfahah method in memorizing Al-Qur`an juz 30 in early childhood at RA Al-Firdaus. The research method used in this study is a type of qualitative research with a descriptive approach. The results of this study indicate that in the implementation of the musyāfahah method at RA Al-Firdaus, namely students and teachers face to face or in a circle then the teacher gives an example of reading the verse to be memorized and then the students imitate the verse together until they memorize it and then take turns reciting the memorization between one student and another. In increasing the memorization of the Al-Qur`an juz 30 in early childhood at RA Al-Firdaus it can be done by planning targets to be memorized, implementing effective methods of memorizing, and evaluating the memorization of each student. the implementation of the musyāfahah method at RA Al-Firdaus is quite effective and successful, as can be seen from the achievement of the 2021/2022 target, there are 52% of students who can complete juz 30 within 2